Quantitative study on the characteristics of dynamic vehicle interference to geomagnetic field - Qin Tian; Xiujuan Hu; Guoping Chang; Shaopeng He; Pengkun Guo (地震科学进展)
In recent years, geomagnetic observation stations have been subjected to more and more serious interference by HVDC transmission, subway, vehicles, etc. About 35 of the national geomagnetic second sampling stations have been subjected to vehicle interference, which has affected the integrity and efficiency of geomagnetic observation data. In this paper, three GM4 fluxgate magnetometers are used to carry out field interference tests on different types of vehicles in different directions, at different distances and at different speeds at Hongshan geomagnetic station, and the quantitative changes of horizontal component H, vertical component Z and magnetic declination angle D of geomagnetic field are analyzed. The results show that the dynamic vehicle driving orientation can be determined by the variation pattern of geomagnetic declination D component, and the influence of dynamic vehicle speed on geomagnetic field is small in space. A mathematical model of vehicle position change in geomagnetic field is established. Three fluxgate magnetometers can be used to invert the vehicle driving direction, driving speed and relative observation instrument position changes caused by geomagnetic stations. It provides a reference for the geomagnetic station to identify the impact of vehicle interference.